THE EFFECT OF EDUCATION USING MODIFICATION MODULE TOWARDS NUTRITIONAL INTAKE DURING PREGNANCY IN KENDARI, INDONESIA - Kartini, Kartini; Syafar, Muh; Arsin, Arsunan A.; Bahar, Burhanuddin; Farming, Farming; Fitriyanti, Fitriyanti (YCAB Publisher & IAKMI SULTRA, 2016)
Background: Energy metabolism speeds up during pregnancy that requires pregnant women to have extra amount of nutritions. Provision of education on nutrition during pregnancy is an effort to prevent and tackle malnutrition.Aim: This study aimed to determine the effect of education using modification module towards nutritional intake during pregnancy in Kendari, IndonesiaMethods: This was Quasi Experimental study with pre-post design. There were 4 groups in this study, which were: 1) The group that received educational intervention using a modification module from the MHC book of the Department of Health, 2) The group that received educational intervention using MHC book of the Department of Health, 3) The group that only used modification modules from MHC book of the Department of Health, and 4) The group that only used the MHC book of Department of Health. The intervention was given for 6 months. Seventy eight of 4-months pregnant women were selected in this study. Data were collected by using 24 hours food recall instrument, and questionnaire adopted from Child and Maternal Nutrition Survey's Questionnaire of Faculty of Public Health, Hasanuddin University. Data were analyzed by using Wilcoxon test and Kruskal Wallis test.Results: Results showed there was an effect of education by using the module modifications to the intake of nutritions during pregnancy. Increased nutrient intake was higher in pregnant women using a module class modifications.Conclusion: Education affects nutritional intake of pregnant women. Changes in nutritional intake was higher in group 1 (education modules with modifications), compared with the education group MCH handbook. It is suggested that mothers should improve the nutrition during pregnancy for the better growth of the fetus, composition and metabolic changes in the mother's body.